Impacts of Risk Perception, Disaster Knowledge, and Emotional Attachment on Tourists’ Behavioral Intentions in Qinling Mountain, China - Hao, Junqing; Tang, Han; Hao, Jiawei; Ma, Yanting; Jiang, Xinxiang (Frontiers in Earth Science, 2022)
With natural disasters occurring more frequently in the global, their impact on tourism activities is becoming a serious challenge. The existing literature in the field of tourism disaster management focus mostly on disaster impact analysis, risk assessment and post-disaster recovery while the impact of disaster on tourism and tourists is still a new topic. It is necessary to investigate the correlation between the natural disasters and the tourists’ behavior. Taking the famous tourism destination—Qinling Mountain, located in the middle of China, as an example where frequent mountain disasters happened, we investigate 542 youth group tourists by a questionnaire survey, and analyze the influence of risk perception, disaster knowledge and emotional attachment on tourists’ travel behavioral intentions. The results showed that: 1) risk perception has a negative effect on tourists’ behavioral intentions; 2) disaster knowledge and tourism emotional attachment have a positive effect on tourists’ behavioral intention; 3) the moderation role of gender is not significant, while the moderation role of educated level is significant. Therefore, this analysis is of great importance for research dealing with the theory of tourism disaster and the management practice of disaster-oriented tourism destinations.